2008
DOI: 10.1111/j.1464-5491.2008.02583.x
|View full text |Cite
|
Sign up to set email alerts
|

Children and young people with diabetes in Yorkshire: a population‐based clinical audit of patient data 2005/2006

Abstract: Our population-based clinical audit of children with diabetes is the product of an effective collaboration between those who deliver care and health services researchers. High levels of recording the key care process measuring diabetes control, compared with national figures, suggests collaboration has translated into improved services. The interesting association between poor diabetes control and higher deprivation is noteworthy and requires further investigation. Future audits require recording of clinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 14 publications
(17 reference statements)
1
14
1
Order By: Relevance
“…Studies performed in the UK and France indicate that older age and longer duration of diabetes is associated with poor glycaemic control [21]. This contrasts with a study by Elbargi et al [34] among insulin dependent type 1 diabetics in Sudan describing a higher incidence of poor glycaemic control among younger type 1 diabetics.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Studies performed in the UK and France indicate that older age and longer duration of diabetes is associated with poor glycaemic control [21]. This contrasts with a study by Elbargi et al [34] among insulin dependent type 1 diabetics in Sudan describing a higher incidence of poor glycaemic control among younger type 1 diabetics.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, diabetes-related characteristics including; frequency of self-monitoring of blood glucose [4, 17, 18], diet [19], diabetes duration [20, 21], regularity of clinic visits [22, 23, 24], insulin regimen [6] and family involvement in diabetes related tasks [25] are also associated with the level of glycaemic control of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Only one of the cohort studies had a high quality , while the other nine cohort studies were of moderate quality. Three cross‐sectional studies were scored to have a low risk of bias, two of which reached the optimal rating .…”
Section: Resultsmentioning
confidence: 99%
“…Indices of area‐level socio‐economic status or deprivation included measures like the Socio‐Economic Indexes for Areas , the Townsend Deprivation Score or comparable indices. Townsend defined (area‐level) deprivation ‘as a state of observable and demonstrable disadvantage relative to the local community or the wider society or nation to which an individual, family or group belongs’ .…”
Section: Methodsmentioning
confidence: 99%
“…An increasing duration of diabetes was significantly associated with poorer control demonstrated in a population-based UK study of 1,742 children and young people with T1D. The authors of this study reported a 0.08% rise in A1C for every additional year of diabetes duration (McKinney et al, 2008). The pattern of worsening glycemic control with increased duration of diabetes is due in part to progressive loss of beta cell function but also contributing may be the difficulty in maintaining motivation for daily diabetes care over time (Petitti et al, 2009;Scholin et al, 2004).…”
Section: Diabetes Durationmentioning
confidence: 72%